2018
DOI: 10.1002/bies.201700223
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitylation Pathways In Insulin Signaling and Organismal Homeostasis

Abstract: The insulin/insulin-like growth factor-1 (IGF-1) signaling (IIS) pathway is a pivotal genetic program regulating cell growth, tissue development, metabolic physiology, and longevity of multicellular organisms. IIS integrates a fine-tuned cascade of signaling events induced by insulin/IGF-1, which is precisely controlled by post-translational modifications. The ubiquitin/proteasome-system (UPS) influences the functionality of IIS through inducible ubiquitylation pathways that regulate internalization of the ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 114 publications
0
17
0
Order By: Relevance
“…FoxO1, β-arrestin, IRS and IGF1R are all crucial to maintaining an efficient insulin signal (Usui et al, 2004;Girnita et al, 2007). Interestingly, these proteins might compete for binding to MDM2 (Balaji et al, 2018). Yet, the role of cardiac MDM2 in diabetic cardiomyopathy remains unclear.…”
Section: Nuclear Downstream Targets Of Mdm2 Mdm2-foxo Proteins Interamentioning
confidence: 99%
“…FoxO1, β-arrestin, IRS and IGF1R are all crucial to maintaining an efficient insulin signal (Usui et al, 2004;Girnita et al, 2007). Interestingly, these proteins might compete for binding to MDM2 (Balaji et al, 2018). Yet, the role of cardiac MDM2 in diabetic cardiomyopathy remains unclear.…”
Section: Nuclear Downstream Targets Of Mdm2 Mdm2-foxo Proteins Interamentioning
confidence: 99%
“…The ubiquitin-proteasome system, which regulates cellular protein degradation, plays a pivotal role in cellular homeostasis 30 . Previous studies have shown that AHR acts as an E3 ubiquitin ligase to modulate steroid receptor functions 31 .…”
Section: Discussionmentioning
confidence: 99%
“…CHIP is an E3 ubiquitin ligase that plays a pivotal role in the protein quality control system by shifting the balance of the folding-refolding machinery toward the degradative pathway in order to maintain balanced proteostasis networks (33,(210)(211)(212). CHIP is highly expressed in tissues with high metabolic activity and protein turnover.…”
Section: Chip and Ghrmentioning
confidence: 99%
“…Remarkably, transcription of CHIP is also modulated in response to changes in AKT levels (215). Similar to AKT regulation, CHIP indirectly impacts the FOXO function on various levels through modulation of upstream substrates of the insulin/IGF-1 signaling pathway, a pivotal genetic program regulating cell growth, tissue development, metabolic physiology, and longevity of multicellular organisms (210). Thus, CHIP integrates proteostasis and aging by regulation the turnover of the INSR (211).…”
Section: Chip and Ghrmentioning
confidence: 99%
See 1 more Smart Citation